Peningkatan aktivitas dan hasil belajar tentang pecahan dengan menggunakan media manipulatif dari kertas siswa sekolah dasar - Erni Yanti (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2018)
The study was conducted on third-grade students of SD Negeri 12 Api - Api Kecamatan Bayang in the lesson of 2016/2017 using classroom action research (PTK). The study was conducted in two cycles. The instruments used to collect data are test sheets and observation sheets. The results showed an increase in cycles, I and II, so it can be concluded that paper manipulative media can increase student activity and learning outcomes about fractions.